Investigating the mycobiome of the Holcomb Creosote Superfund Site. (August 2020) - Czaplicki, Lauren M.; Redfern, Lauren K.; Cooper, Ellen M.; Ferguson, P. Lee; Vilgalys, Rytas; Gunsch, Claudia K.
Abstract: Even though many fungi are known to degrade a range of organic chemicals and may be advantageous for targeting hydrophobic chemicals with low bioavailability due to their ability to secrete extracellular enzymes, fungi are not commonly leveraged in the context of bioremediation. Here we sought to examine the fungal microbiome (mycobiome) at a model creosote polluted site to determine if fungi were prevalent under high PAH contamination conditions as well as to identify potential mycostimulation targets. Several significant positive associations were detected between OTUs and mid-to high-molecular weight PAHs. Several OTUs were closely related to taxa that have previously been identified in culture-based studies as PAH degraders. In particular, members belonging to the Ascomycota phylum were the most diverse at higher PAH concentrations suggesting this phylum may be promising biostimulation targets. There were nearly three times more positive correlations as compared to negative correlations, suggesting that creosote-tolerance is more common than creosote-sensitivity in the fungal community. Future work including shotgun metagenomic analysis would help confirm the presence of specific degradation genes. Overall this study suggests that mycobiome and bacterial microbiome analyses should be performed in parallel to devise the most optimal in situ biostimulation treatment strategies. Graphical abstract: Image 1 Highlights: Fungi are underutilized in bioremediation scenarios. We validated a novel strategy to detect mycostimulation targets at a creosote site. Significant positive associations exist between indigenous fungi and PAHs. There were many site fungi closely related to known PAH degraders. Ascomycota was the most diverse clade at high PAH levels and may hold good targets.